Subdaily‐Scale Chemical Variability in a Torreites Sanchezi Rudist Shell: Implications for Rudist Paleobiology and the Cretaceous Day‐Night Cycle. Issue 2 (18th February 2020) - de Winter, Niels J.; Goderis, Steven; Van Malderen, Stijn J.M.; Sinnesael, Matthias; Vansteenberge, Stef; Snoeck, Christophe; Belza, Joke; Vanhaecke, Frank; Claeys, Philippe
Abstract: This study presents subdaily resolved chemical records through fossil mollusk shell calcite. Trace element profiles resolve periodic variability across 40‐μm‐thin daily growth laminae in a Campanian Torreites sanchezi rudist bivalve. These high‐resolution records are combined with seasonally resolved stable isotope and trace element records that allow shell‐chemical variability to be discussed on both seasonal and daily scale. A combination of layer counting, spectral analysis of chemical cyclicity and chemical layer counting shows that the rudist precipitated 372 daily laminae per year, demonstrating that length of day has increased since the Late Cretaceous, as predicted by astronomical models. This new approach to determine the length of a solar day in geologic history through multiproxy chemical records at subdaily resolution yields considerably more control on the uncertainty of this estimate. Daily chemical variability exceeds seasonal variability in our records, and cannot be explained by diurnal temperature changes. Instead, we postulate that rudist shell chemistry is driven on a daily scale by changes in light intensity. These results together with those of stable isotope analyses provide strong evidence that Torreites rudists had photosymbionts. Bivalve shell calcite generally preserves well. Therefore, this study paves the way for daily‐scale reconstructions of paleoenvironment and sunlight intensity on geologic time scales from bivalve shells, potentially allowing researchers to bridge the gap between climate and weather reconstructions. Such reconstructions improve shell chronologies, document environmental change in warm ecosystems, and widen our understanding of the magnitude of short‐term changes during greenhouse climates. Key Points: High‐resolution LA‐ICP‐MS profiles reveal strong diurnal cyclicity in rudist shell Dominance of day‐night cycle suggests photosymbiosis in the rudist species Torreites sanchezi Length of annual and daily cycle is used to constrain Campanian Earth‐Moon distance